2022
DOI: 10.1038/s41592-022-01684-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of extracellular proteins, protein complexes and mRNAs in single cells by proximity sequencing

Abstract: †Indicates equal contribution Multiplexed analysis of single-cells enables accurate modeling of cellular behaviors, classification of new cell types, and characterization of their functional states. Here we present proximity-sequencing (Prox-seq), a method for simultaneous measurement of an individual cell's proteins, protein complexes and mRNA. Prox-seq utilizes deep sequencing and barcoded proximity assays to measure proteins and their complexes from all pairwise combinations of targeted proteins, in thousan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…We found that VEGFA transcripts and VEGF-A secretion have very low correlation in normoxic and hypoxic MSCs. While surprising, the uncoupling of transcript level and protein secretion is in line with similar studies using CITE-seq where certain surface protein and transcripts feature low correlation 14,15,45 .…”
Section: Discussionsupporting
confidence: 84%
“…We found that VEGFA transcripts and VEGF-A secretion have very low correlation in normoxic and hypoxic MSCs. While surprising, the uncoupling of transcript level and protein secretion is in line with similar studies using CITE-seq where certain surface protein and transcripts feature low correlation 14,15,45 .…”
Section: Discussionsupporting
confidence: 84%
“…One of the advantages of using padlock probes is the power of signal amplification by RCA. Therefore, ARTseq-FISH has the potential to detect DNA (i.e., single nucleotide polymorphisms (SNPs)) 74 , miRNAs 75, 76 , viral RNA 77 , and proximity of proteins 37, 78 or even proximity of RNA and protein. In addition, due to the signal amplification of RCA, the results of ARTseq-FISH can also be read out by flow cytometry 79, 80 , which makes this and future techniques more broadly accessible.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the resolution of protein detection is often below the level of RNA detection proving a barrier to quantitative insights into protein location or spatial correlation of RNA and protein abundance 24,26,[28][29][30][31][32] . Conversely, DNA-barcoding dependent methods (for example, CODEX 33 , ImmunoSABER 34 and InSituPlex® 35 ) have shown their multiplexing capacity in protein detection, but have thus far not been integrated with RNA detection 36,37 .…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the roles of protein interactions in greater depth, we recently developed a method called proximity sequencing (Prox-seq) for simultaneous quantification of mRNA, surface proteins and protein complexes at the single-cell level [ 4 ] Prox-seq captures protein complex information in barcoded DNA oligonucleotides (oligos) using a proximity ligation assay [ 5 , 6 ] (PLA). Each protein in Prox-seq is targeted by two DNA-conjugated antibodies, called Prox-seq probes A and B ( Fig 1a ).…”
Section: Introductionmentioning
confidence: 99%